2015
DOI: 10.1016/j.celrep.2015.09.073
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 Regulates the Differentiation and Function of Intestinal Dendritic Cells and Macrophages by Targeting C/EBPβ

Abstract: Dendritic cells (DCs) and macrophages play important roles in maintaining intestinal homeostasis. However, the molecular mechanisms that regulate the differentiation and responses of intestinal DCs and macrophages remain poorly understood. Here, we have identified microRNA miR-223 as a key molecule for regulating these processes. Deficiency of miR-223 led to a significantly decreased number of intestinal CX3CR1(hi) macrophages at steady state. Both intestinal CX3CR1(hi) macrophages and CD103(+) conventional DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 54 publications
3
90
1
1
Order By: Relevance
“…Interestingly, treadmill exercise training also down-regulated the C/EBP␤ expression in hearts (Fig. 8F), which is consistent with our miR-223 TG mouse model as well as previous publication (16). Thus, miR-223-induced physiological hypertrophy also may be attributed to the reduction of C/EBP␤.…”
Section: Volume 291 • Number 30 • July 22 2016supporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, treadmill exercise training also down-regulated the C/EBP␤ expression in hearts (Fig. 8F), which is consistent with our miR-223 TG mouse model as well as previous publication (16). Thus, miR-223-induced physiological hypertrophy also may be attributed to the reduction of C/EBP␤.…”
Section: Volume 291 • Number 30 • July 22 2016supporting
confidence: 79%
“…Nonetheless, recent work has implicated that several bona fide targets of miR-223 (e.g. IGF-1R and C/EBP␤) (15,16) are associated with physiological cardiac hypertrophy, but their functional consequences appear to be counteracted. For example, up-regulation or activation of IGF-1R has been widely proposed to facilitate developmental growth and physiological hypertrophy of the heart (17,18).…”
mentioning
confidence: 99%
“…On the other hand, dendritic cell (DC) and macrophages are also crucial in the maintenance of intestinal immune homeostasis . Given the fact that miR‐223 modulates the differentiation of monocytes, several studies have indicated the involvement of miR‐223 in the regulation of innate immunity in IBD . Although miR‐223 deficiency in mice resulted in reduction of CX3CR1hi macrophages at steady state, both CX3CR1 hi macrophage and CD103 + DCs showed a pro‐inflammatory phenotypes.…”
Section: Functional Roles Of Myeloid Mir‐223 During Inflammatory Disementioning
confidence: 99%
“…Research in the mechanism of miR-223 found that it could target C/EBPβ, E2F1, FOXO1, NFI-A, and MAFB to inhibit tumor cell proliferation, migration, and invasive capability in vitro;2630 however, it could also deregulate the expression of tumor suppressors 3133. As miR-223 affects multiple targets simultaneously that are involved in key processes,14 the role of miR-223 in cancer depends on the type of cancer and the total level in patient’s body.…”
Section: Discussionmentioning
confidence: 99%